Greco-Roman Wrestling Techniques, Classification, Systematics and Their Terminology General Rules (Texas Journal of Multidisciplinary Studies, 2022)
The following points provide information and suggestions on Greco-Roman wrestling techniques, classification, systematics and terminology, and general rules